Association Between Personal Hygiene Practices and Peripheral Blood Profiles in Agrarian Workers: An Analysis with Socio-demographic and Helminthiasis Considerations - Indiastari, Dewi; Didi Candradikusuma; Milanitalia Gadys Rosandy; Niniek Budiarti; Heri Sutanto; Sinta Silvia (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Helminthiasis remains a significant public health issue in Indonesia, negatively impacting nutrition and cognitive development, particularly among individuals who are in direct contact with soil. To mitigate this issue, improving personal hygiene and awareness of infection prevention is essential. This study aims to examine the correlation between sociodemographic factors and personal hygiene with blood profiles among workers in agrarian areas. Methods: A cross-sectional approach was used, with 144 samples collected through purposive sampling in the agrarian area of Malang Regency. Data were gathered using questionnaires covering sociodemographic factors and personal hygiene, as well as through hematology tests results obtained from blood samples taken from respondents, which were tested at the dr. Saiful Anwar Malang General Hospital. For data analysis, the Chi-square test was utilized for bivariate analysis, while logistic regression was employed for multivariate analysis. Results: The mean age of respondents was 48.1 ± 14.1 years, with a majority having attained only an elementary education (51.4%) and primarily working as farmers (66.7%). Approximately 38.2% of respondents demonstrated poor personal hygiene. Significant associations were found between personal hygiene and hemoglobin levels (p=0.031), as well as eosinophil counts (p=0.007). Multivariate analysis showed that respondents who did not wash their hands before eating had 1.8 times higher odds of having abnormal blood profiles compared to those who practiced handwashing. Conclusion: The results of this study suggest that sociodemographic factors and personal hygiene are associated with the quality of blood profile among respondents. Enhanced education is needed to raise community awareness regarding personal hygiene.